Pseudo-Slant submaniolds of nearly δ- Lorentzian trans Sasakian manifolds - Shamsur Rahman (Journal of Hyperstructures, 2025)
Our focus is on the existence of certain structures and similarities between pseudo slant submanifolds and nearly δ- Lorentzian trans Sasakian manifolds. We examine the geometry of these submanifolds.For a totally umbilical proper-slant submanifold that corresponds to a nearly δ- Lorentzian trans Sasakian manifold, we demonstrate necessary and sufficient conditions. Finally, we talk about the integrability of distributions on approximately δ- Lorentzian trans Sasakian manifold pseudo-slant submanifolds.